Noise Exposure and Hearing Loss among Workers at a Hammer Forge Company - Brueck, Scott E.; Eisenberg, Judith; Zechmann, Edward L.; Murphy, William J.; Krieg, Edward; Morata, Thais C. (Seminars in Hearing, 2023)
The National Institute for Occupational Safety and Health (NIOSH) evaluated continuous and impact noise exposures and hearing loss among workers at a hammer forge company. Full-shift personal noise exposure measurements were collected on forge workers across 15 different job titles; impact noise characteristics and one-third octave band noise levels were assessed at the forge hammers; and 4,750 historic audiometric test records for 483 workers were evaluated for hearing loss trends. Nearly all workers' noise exposures exceeded regulatory and/or recommended exposure limits. Workers working in jobs at or near the hammers had full-shift time-weighted average noise exposures above 100 decibels, A-weighted. Impact noise at the hammers reached up to 148 decibels. Analysis of audiometric test records showed that 82% of workers had experienced a significant threshold shift, as defined by NIOSH, and 63% had experienced a standard threshold shift, as defined by the Occupational Safety and Health Administration (OSHA). All workers with an OSHA standard threshold shift had a preceding NIOSH significant threshold shift which occurred, on average, about 7 years prior. This evaluation highlights forge workers' exposures to high levels of noise, including impact noise, and how their hearing worsened with age and length of employment.
Keywords: noise; impact noise; noise-induced hearing loss; hearing loss; hammer forge